Examination of Selected Synthesis Parameters for Composite Adhesive-type Urea-Formaldehyde/activated Carbon Adhesives - Gupta, Arun; Tanveer, Ahmad Khan; Saidatul Shima, Jamari; Rajan, Jose (Penerbit Universiti Malaysia Pahang, 2015)
This paper addresses synthesis of activated carbon particles by pyrolysis of wood fibers and their dispersion in urea formaldehyde with an aim to optimize a stable activated carbon particles/urea formaldehyde adhesives. All the adhesive hybrids were characterized with X-ray diffractometry (XRD) Fourier transform infrared spectroscopy (FTIR), while the dispersion of activated carbon particles was studied with Field Emission scanning electron microscopy (FESEM). Thermo gravimetric analysis (TGA) shows that activated carbon particles have little high effect in the thermal stability of the UF adhesive. It is observe in the TGA graph that the thermal stability of the UF based activated carbon particles is higher that UF only. The scanning micrograph provide confirmation of the smoother surfaces in the UF adhesive made with activated carbon particles.